Dynamic selection for forage quality and quantity in response to phenology and insects in an Arctic ungulate. Issue 17 (4th August 2021) - Johnson, Heather E.; Golden, Trevor S.; Adams, Layne G.; Gustine, David D.; Lenart, Elizabeth A.; Barboza, Perry S.
Abstract: Spatiotemporal variation in forage is a primary driver of ungulate behavior, yet little is known about the nutritional components they select, and how selection varies across the growing season with changes in forage quality and quantity. We addressed these uncertainties in barren‐ground caribou ( Rangifer tarandus ), which experience their most important foraging opportunities during the short Arctic summer. Recent declines in Arctic caribou populations have raised concerns about the influence of climate change on summer foraging opportunities, given shifting vegetation conditions and insect harassment, and their potential effects on caribou body condition and demography. We examined Arctic caribou selection of summer forage by pairing locations from females in the Central Arctic Herd of Alaska with spatiotemporal predictions of biomass, digestible nitrogen (DN), and digestible energy (DE). We then assessed selection for these nutritional components across the growing season at landscape and patch scales, and determined whether foraging opportunities were constrained by insect harassment. During early summer, at the landscape scale, caribou selected for intermediate biomass and high DN and DE, following expectations of the forage maturation hypothesis. At the patch scale, however, caribou selected for high values of all forage components, particularly DN, suggesting that protein may be limiting. During late summer, after DN declined below the threshold for protein gain, caribou exhibited a switch at both spatial scales, selecting for higher biomass, likely enabling mass and fat deposition. Mosquito activity strongly altered caribou selection of forage and increased their movement rates, while oestrid fly activity had little influence. Our results demonstrate that early and late summer periods afford Arctic caribou distinct foraging opportunities, as they prioritize quality earlier in the summer and quantity later. Climate change may further constrain caribou access to DN as earlier, warmer Arctic summers may be associated with reduced DN and increased mosquito harassment. Abstract : We examined the summer foraging behavior of Arctic caribou to assess selection for different nutritional components across the growing season at landscape and patch scales, and determine whether foraging opportunities were constrained by insect harassment. We found that caribou selected for forage quality early in the summer likely enabling protein deposition, while they selected for forage quantity later in the summer likely enabling fat deposition. Mosquito harassment strongly altered caribou selection of forage and increased their energy expenditure, while oestrid fly harassment had relatively little influence.